Efektivitas Model Pembelajaran Teaching Games for Understanding (TGfU) dalam Permainan Invasi terhadap Keterampilan Motorik Kasar dan Decision Making pada Siswa Sekolah Dasar - Muhammad Hafidz Ramadhan; Wulandari Putri; Yogi Akin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the effectiveness of the Teaching Games for Understanding (TGfU) learning model in invasion games on gross motor skills and decision-making ability of elementary school students. The research method used was an experiment with a one-group pretest-posttest design. The research subjects consisted of 32 fourth-grade students of SDN 032 Tilil Bandung City aged 9–10 years, selected using a purposive sampling technique. The treatment was given in 8 sessions. The instruments used were the Test of Gross Motor Development-Second Edition (TGMD-2) to measure gross motor skills and the Game Performance Assessment Instrument (GPAI) to measure decision-making ability. The Shapiro–Wilk test results showed that motor skills data were normally distributed (p > 0.05), while decision-making data were not normally distributed (p < 0.05). Hypothesis testing used the Paired Samples T-Test for motor skills and the Wilcoxon Signed Ranks Test for decision making. The results showed a significant improvement in gross motor skills and decision-making ability after the implementation of the TGfU model. Thus, the TGfU learning model in invasion games proved to be effective in improving gross motor skills and decision-making ability of elementary school students. Keywords: Decision Making, Gross Motor Skills, Invasion Games, Teaching Games for Understanding